2012
DOI: 10.1155/2012/815079
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Thyroid Papillary Carcinoma

Abstract: Papillary thyroid carcinoma (PTC) is the most common endocrine malignancy. We performed shotgun liquid chromatography (LC)/tandem mass spectrometry (MS/MS) analysis on pooled protein extracts from patients with PTC and compared the results with those from normal thyroid tissue validated by real-time (RT) PCR and immunohistochemistry (IHC). We detected 524 types of protein in PTC and 432 in normal thyroid gland. Among these proteins, 145 were specific to PTC and 53 were specific to normal thyroid gland. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Together, these data are consistent with a model in which miR-26a suppresses CKS2 expression, leading to suppressed of cyclin B1 and cdk1 expression and G 2 arrested, similar to the findings of a previous study [15]. Moreover, consistent with the previous data [16], our results indicate that miR-26a induced cell apoptosis involves by Bcl-xl and Akt, which are mainly involved in programmed cell death.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Together, these data are consistent with a model in which miR-26a suppresses CKS2 expression, leading to suppressed of cyclin B1 and cdk1 expression and G 2 arrested, similar to the findings of a previous study [15]. Moreover, consistent with the previous data [16], our results indicate that miR-26a induced cell apoptosis involves by Bcl-xl and Akt, which are mainly involved in programmed cell death.…”
Section: Discussionsupporting
confidence: 93%
“…PTC is the most common form of follicular-cell derived carcinomas and comprises 75% of all newly-diagnosed thyroid cancers [16]. While studies have shown that miR-26a is down-regulated in PTC [4], [5], [6], [7], [8], to date no data have been available regarding the mechanism of miR-26a in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies of the thyrocyte and thyroid cancer proteomics, both ex vivo [26][27][28][29] and of cell lines [25] are in a minority compared with studies of the genome and transcriptome [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…MLEC is an endoplasmic reticulum-resident lectin participating in the identification and degradation of misfolding glycoproteins. Overexpression of MLEC was considered as one of the new markers in papillary thyroid carcinoma (Ban et al, 2012). Downregulation of hsa-miR-133a-3p has already been determined as a selective marker in colon cancer (Weber et al, 2018).…”
Section: Discussionmentioning
confidence: 99%